Scaling Climate Resilient Seeds Through Inclusive Agri-businesses in East Africa - Shilomboleni, Helena; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In East Africa, the (exclusive) development of formal seed systems has not seen widespread adoption of improved, certified seeds among smallholder farmers, contributing less than 20% of seed use for staple crops. There are various reasons for such limited impact, including neglect of social system dynamics in the multiplication and eventual delivery of seeds to smallholder farmers. This InfoNote shares CRAFT project experiences of scaling climate-resilient seeds in East Africa, leveraging on farmer agency and inclusive business practices to strengthen the performance of existing seed systems for certified, Quality Declared Seeds (QDS)and clean seeds through complementarity. Multiple CRAFT-supported SME business champions built the capacity of community seed growers to supply climate-resilient seeds for a broader base of smallholder farmers. These inclusive climate-smart agri-business efforts, when combined with an appreciation for system dynamics of intervention contexts, can help bring about effective scaling strategies with the potential to achieve impact at scale.